Effects of organic matter and mineral compositions on pore structures of shales: A comparative study of lacustrine shale in Ordos Basin and Marine Shale in Sichuan Basin, China. Issue 1 (January 2018) - Tang, Xianglu; Jiang, Zhenxue; Jiang, Shu; Li, Zhuo; Peng, Yongmin; Xiao, Dianshi; Xing, Fengcun
The pore structure of shale plays key role in oil and gas storage capacity and accumulation. Twelve representative samples were selected from Triassic Yanchang Formation in the Ordos Basin and Silurian Longmaxi Formation in the Sichuan Basin with different ages, depositional settings, and maturities to analyze shale pore structure using focused ion beam-scanning electron microscopy and high-pressure mercury intrusion capillary porosimetry. The results show that the pores of lacustrine shale with maturity Ro < 1.3% from the Triassic Yanchang Formation were predominantly composed of pores with pore throat diameter of larger than 30 µm. The pores of marine shale with maturity Ro > 1.3% from the Silurian Longmaxi Formation were predominantly composed of pores with pore throat diameter of smaller than 100 nm. For the porosity, the average porosity of low-mature lacustrine shale is 2.4%, while the average porosity of high-mature marine shale is 1.5%. For the pore type, intergranular inorganic pores predominantly occurred between mineral particles in the lacustrine shale, while the marine shale mainly developed organic pores with pore throat diameters ranging from 5 to 200 nm. Compared to the low-mature lacustrine shale, macropores of high-mature marine shale are less developed and micropores dominant. Importantly, brittle minerals (quartz, feldspar, and carbonate minerals) mainly affect the pore structure of lacustrine shale, while organic matter mainly affects the pore structure of marine shale.